Nasal polyposis in cystic fibrosis: follow-up of children and adolescents for a 3-year period - Theresa Weber, Silke Anna [UNESP]; Iyomasa, Renata Mizusaki [UNESP]; Correa, Camila de Castro [UNESP]; Mafra Florentino, Wellington Novais [UNESP]; Ferrari, Giesela Fleischer [UNESP] (Assoc Brasileira Otorrinolaringologia & Cirurgia Cervicofacial, 2017)
Introduction : Nasal polyposis is often found in patients with cystic fibrosis. Objective : To assess the incidence of nasal polyposis, the response to medical treatment, recurrence and the need for surgical intervention in children and adolescents with cystic fibrosis during a three-year follow-up. Methods : Clinical symptoms (pulmonary, pancreatic insufficiency, malnutrition, nasal obstruction), two positive sweat chloride tests, and genotype findings in 23 patients with cystic fibrosis were analyzed. All patients underwent nasal endoscopy every 12 months from January 2005 to December 2007, to assess the presence and grade of Nasal Polyps. Nasal polyposis, when present, were treated with topical corticosteroids for 6-12 months, with progress being evaluated within the 3 years of follow-up. Results : In the first evaluation, nasal polyposis was diagnosed in 30.43% of patients (3 bilateral and 4 unilateral), recurrent pneumonia in 82.6%, pancreatic insufficiency in 87%, and malnutrition in 74%. The presence of nasal polyposis was not associated with chloride values in the sweat, genotype, clinical signs of severity of cystic fibrosis, or nasal symptoms. In the three-year period of follow up, 13 patients (56.52%) had at least one event of polyposis, with the youngest being diagnosed at 32 months of age. Only one patient underwent surgery (polypectomy), and there was one diagnosis of nasopharyngeal carcinoma. Conclusion : The study showed a high incidence of nasal polyposis. Monitoring through routine endoscopy in patients with cystic fibrosis, even in the absence of nasal symptoms, is highly recommended. The therapy with topical corticosteroids achieved good results. Thus, an interaction between pediatricians and otolaryngologists is necessary. (C) 2016 Associacao Brasileira de Otorrinolaringologia e Cirurgia Cervico-Facial. Published by Elsevier Editora Ltda.
Keywords: Polyposis; Cystic fibrosis; Diagnosis; Endoscopy; Therapy